INCIDENCE OF SURGICALLY ASSISTED ORTHODONTIC TOOTH ERUPTION-A RETROSPECTIVE INSTITUTIONAL STUDY - Shree. P, Chaitanya; M. , Sivakumar; . R, Subhashree (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The most commonly impacted teeth are molar and maxillary canine impactions. Surgically assisted orthodontic eruption is the surgical uncovering of the crown that aids in tooth eruption, and it is the commonly employed method for tooth eruption. The present study aims at assessing the incidence of surgically assisted orthodontic tooth eruptions at Saveetha Dental College.Materials and methods: The present study is a retrospective-based analysis conducted in a hospital setting. Patient records were collected by a complete analysis of data from 86,000 patients between March 2019 and March 2020. The required data were extracted from the patient’s records. 19 case sheets were collected. The data collected are stored in Excel and transferred to SPSS for analysis by T-test. A chi-square test was done to associate age and gender with the affected tooth group. Results obtained in the form of bar graphs.Results: 19 patients who underwent surgical-orthodontic eruptions were used for this study. In the present study, we observed that 11- to 15-year-old patients (42.1%) are more prone to impaction, and the most commonly affected gender is females (73.7%). The commonly affected teeth in the present study were 13-23 (57.9%), especially canines. Associating the age group with the affected teeth group, a p-value was analyzed, and it was found to be statistically significant (p 0.05).Conclusion: In the present study, we observed that patients between 11 and 15 years were more commonly affected by impacted teeth and underwent orthodontic-surgical eruption. Females are more commonly affected than males.